Bildgeführte Strahlentherapie = Image-guided radiation therapy - Boda-Heggemann, Judit; Wertz, Hansjörg; Blessing, Manuel; Wenz, Frederik; Lohr, Frank (Der Radiologe, 2012)
Radiotherapy technology has improved rapidly over the past two decades. New imaging modalities, such as positron emission (computed) tomography (PET, PET-CT) and high-resolution morphological and functional magnetic resonance imaging (MRI) have been introduced into the treatment planning process. Image-guided radiation therapy (IGRT) with 3D soft tissue depiction directly imaging target and normal structures, is currently replacing patient positioning based on patient surface markers, frame-based intracranial and extracranial stereotactic treatment and partially also 2D field verification methods. On-line 3D soft tissue-based position correction unlocked the full potential of new delivery techniques, such as intensity-modulated radiotherapy, by safely delivering highly conformal dose distributions that facilitate dose escalation and hypofractionation. These strategies have already resulted in better clinical outcomes, e.g. in prostate and lung cancer and are expected to further improve radiotherapy results.
Gesehen am 11.10.2018